The Importance of Podocyte Adhesion for a Healthy Glomerulus - Lennon, Rachel; Randles, Michael J.; Humphries, Martin J. (Frontiers in Endocrinology, 2014)
Abstract Podocytes are specialized epithelial cells that cover the outer surfaces of glomerular capillaries. Unique cell junctions, known as slit diaphragms, which feature nephrin and Neph-familiy proteins in addition to components of adherens, tight and gap junctions, connect adjacent podocyte foot processes. Single gene disorders affecting the slit diaphragm result in nephrotic syndrome in humans, characterized by massive loss of protein across the capillary wall. In addition to specialized cell junctions, interconnecting podocytes also adhere to the glomerular basement membrane (GBM) of the capillary wall. The GBM is a dense network of secreted, extracellular matrix (ECM) components and contains tissue-restricted isoforms of collagen IV and laminin in addition to other structural proteins and ECM regulators such as proteases and growth factors. The specialized niche of the GBM provides a scaffold for endothelial cells and podocytes to support their unique functions and human genetic mutations in GBM components lead to renal failure, thus highlighting the importance of cell-matrix interactions in the glomerulus. Cells adhere to ECM via adhesion receptors including integrins, syndecans and dystroglycan and in particular the integrin heterodimer α3β1 is required to maintain barrier integrity. Therefore the sophisticated function of glomerular filtration relies on podocyte adhesion both at cell junctions and at the interface with the ECM. In health the podocyte coordinates signals from cell-junctions and cell-matrix interactions, in response to environmental cues in order to regulate filtration and as our understanding of mechanisms that control cell adhesion in the glomerulus develops, then insight into the effects of disease will improve. The ultimate goal will be to develop targeted therapies to prevent and repair defects in the filtration barrier and to restore glomerular function.